Swain과 Reason의 휴먼에러 모델을 이용한 전동차 기관사의 인적오류 사고분석에 관한 연구 - 김성지; 이철기; 염병수; 갈원모 (한국설비안전학회지, 2021)
This paper analyzed human error caused by five years of flight (2016-2020) by train drivers in the metropolitan area of Korea Railroad. It was intended to analyze the root causes of the accident and cause of the system and present the direction for efficient and safe operation of the train. The human factors that occurred over the past five years were classified into seven types (passing stop, station stop, stop location violation, platform safety door disturbance, neglect of signal verification, delay of work, and neglect of device handling) and compared with the classification of Reason’s behavior model was analyzed in detail. Swain’s analysis of behavioral factors analyzed that the process was not accurately performed, and Reason’s behavior model analyzed that the process was most error-prone by unintended behavior. Most of the human error is caused by carelessness and is designed to be preventable. Through this study, we intend to present measures to reduce human error of train drivers in the Seoul metropolitan area and contribute to safe operation.
Keywords: Human Error; Root Causes; Behavioral Factors; Swain’s Analysis; Reason's Behavioral Model